P60 Acute lowering of portal pressure in cirrhotic rats by Anti-TNF therapy is associated with reduced NFkB-driven inflammation and improved eNOS function through the asymmetric dimethylarginine-dimethylarginine-diaminohydrolase axis. (16th November 2010) - Sharma, V; Balasubramaniyan, V; Sharma, V; Metha, G; Habtesion, A; Turner, C; Dalton, R N; Davies, N; Jalan, R; Mookerjee, R P
Abstract : Introduction: Anti-TNF (Infliximab) monotherapy has been shown to reduce hepatic inflammation and lower portal pressure in alcoholic hepatitis patients. Although the side effect profile of Infliximab limits its clinical use in these patients, ongoing study of the mechanism of this profound beneficial effect remains important to determine novel pathways and future therapeutic targets. Aim: This study aimed to determine whether reduction of NFkB and its target gene TNFα by Infliximab has favourable effects upon the asymmetric dimethylarginine-dimethylarginine-diaminohydrolase (ADMA-DDAH) axis, increasing NO availability whilst lowering portal pressure in bile duct ligated (BDL) cirrhotic rats. Method: Sham (n=6) and BDL (n=15) rats were compared 4 weeks after BDL surgery (treated with vehicle), and in an additional BDL group (n=6) 72 h after 10 mg/kg daily intraperitoneal Infliximab. Rats underwent direct portal pressure assessment under terminal anaesthesia. Measurements: Plasma ALT (Cobas-Integra analyser); hepatic ADMA (LC/MS/MS); eNOS activity (radiometric assay). Hepatic protein expression for NFkB, TNF-α, inducible NOS (iNOS), 4-hydroxy nonenol (HNE) and DDAH-1 were measured by western blot. Results: ALT was significantly (p<0.0001) higher in BDL rats compared to sham, and reverted to near normal following anti-TNF treatment (p<0.05). Protein expressions for NFkB, its target gene TNF-, iNOS and 4HNE were all significantly increased (p<0.01; p<0.03; p<0.01; p<0.01, respectively) in BDL rat livers compared to sham. Infliximab administration significantly reduced expression of NFkB, TNF-α, iNOS and 4HNE (p<0.03; p<0.03; p<0.05; p<0.05, respectively) compared with vehicle treated BDL. Moreover, hepatic DDAH-1 protein was significantly decreased in BDL rats compared to sham (p<0.01) but this normalised to sham levels after Infliximab. Hepatic ADMA was significantly higher in BDL compared with sham (p<0.0001) and reverted back to sham levels (p<0.001) following anti-TNF therapy. Reduction of inflammatory signalling following anti-TNF therapy restored eNOS activity associated with a significant lowering of portal pressure compared to vehicle treated BDL rats (9.48±0.7 vs13.5±0.6 mm Hg respectively, p=0.001). Conclusion: This study confirms significant lowering of portal pressure following Infliximab therapy in the BDL model of cirrhosis. This beneficial effect is associated with reduced hepatic inflammation and restoration of the abnormal ADMA-DDAH-eNOS axis providing potential new targets for portal hypertension therapy.